Charles DeHaven Jones family papers - Jones, Charles DeHaven, -1877.
Correspondence (1837-1893), map of the Confederate States of America, manuscript and pamphlet on cholera, license to practice medicine in New York, and miscellaneous printed material (1862-1903). Jones's writings include several drafts describing his experiences as a surgeon with the 112th Illinois Infantry and his assignment treating Union soldiers released from the Confederate prison at Andersonville, Ga. Correspondents include Eunice Wood Booker, Julia M. Jones, Alonzo C. Wood, Franklin Wood, and Samuel Wood.
Union Army officer and physician.
Collection material in English.
Keywords: Booker, Eunice Wood -- Correspondence; Jones, Julia M. -- Correspondence; Wood, Alonzo C. -- Correspondence; Wood, Franklin -- Correspondence; Wood, Samuel, -- active 1839-1841 -- Correspondence; Andersonville Prison; United States. -- Army. -- Illinois Infantry Regiment, 112th (1862-1865); Cholera; Physicians -- Licenses -- New York (State); Southern States -- Maps; United States -- History -- Civil War,1861-1865 -- Maps; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War,1861-1865 -- Prisoners and prisons; Army officers; Physicians; Surgeons